EFFECT OF GROUP MATING SCHEMES ON LAMB GROWTH PERFORMANCE - D, Ganbat; B, Mandakh; T, Baldan (Mongolian Journal of Agricultural Sciences, 2018)
The study was aimed to determinate the effect of group mating scheme on lamb growth performance. Rams, representing different group mating scheme, were assigned to mate 60-80 ewes per a ram for a 45-day breeding period. In group mating scheme, each ram is placed in a separate pasture with a group of ewes gathered from participating herders involved in group breeding during mating season. The average birth, weaning and post weaning weight for lambs from the group mating of selected rams to selected ewes involved in the study were 4.4, 33.8 and 40 kg for male lambs and, 4.3, 29.8 and 35.7 kg for ewe lambs respectively. These figures indicate that progeny of that group mating scheme were 0.5 to 6.3 kg for male lambs and 0.6-5.5 kg for ewe lambs heavier than progeny of group mating of selected rams to randomly allocated ewes at different age of growth (P <0.05). Mean values of birth, weaning and post weaning weight of progeny for control group mating were lower (P < 0.05) than those of the progeny for all other groups of mating.